Arbuscular mycorrhizal species vary in their impact on nutrient uptake in sweet corn (Zea mays) and butternut squash (Cucurbita moschata) - Carrara, Joseph E.; Heller, Wade P. (Frontiers in Agronomy, 2022)
An increasing demand for organic produce, coupled with the need to reduce reliance on the diminishing resource of rock phosphate, has bolstered interest in the use of arbuscular mycorrhizae (AMF) as a biofertilizer. AMF are symbiotic fungi that colonize the roots of most crops and transfer nutrients from the soil to their hosts in exchange for carbon. While past studies have shown that mixed AMF communities grown from field soil can increase the yield of many crops, the targeted use of individual AMF species on host plants is a promising avenue to enhance nutrient uptake. We inoculated sweet corn (Zea mays) and butternut squash (Cucurbita moschata) seedlings with nine individual species of AMF and one mixed indigenous population to determine the most beneficial symbionts for enhancing mineral nutrient concentration and yield. Overall, level of root colonization was correlated with phosphorus (P) concentration of aboveground biomass. Corn and squash grown in association with AMF species in the Rhizophagus genus had the highest level of root colonization and tissue P concentration. Claroideoglumus etunicatum and Gigaspora margarita increased calcium (Ca) and magnesium (Mg) concentration in corn and Gigaspora rosea increased calcium in squash. S. constrictum and G. rosea positively impacted sweet corn seedling biomass. Based on this evidence, AMF species vary in their benefit to plant nutrient uptake and the most beneficial species depend on host. Further research on the effectiveness of inoculating individual AMF species across a range of hosts and ecosystems will prove useful in the development of host-targeted AMF biofertilizers.